Intrinsic mechanical behavior of femoral cortical bone in young, osteoporotic and bisphosphonate-treated individuals in low- and high energy fracture conditions - Zimmermann, Elizabeth A. (Sci Rep, 2016)
Bisphosphonates are a common treatment to reduce osteoporotic fractures. This treatment induces osseous structural and compositional changes accompanied by positive effects on osteoblasts and osteocytes. Here, we test the hypothesis that restored osseous cell behavior, which resembles characteristics of younger, healthy cortical bone, leads to improved bone quality. Microarchitecture and mechanical properties of young, treatment-naïve osteoporosis, and bisphosphonate-treated cases were investigated in femoral cortices. Tissue strength was measured using three-point bending. Collagen fibril-level deformation was assessed in non-traumatic and traumatic fracture states using synchrotron small-angle x-ray scattering (SAXS) at low and high strain rates. The lower modulus, strength and fibril deformation measured at low strain rates reflects susceptibility for osteoporotic low-energy fragility fractures. Independent of age, disease and treatment status, SAXS revealed reduced fibril plasticity at high strain rates, characteristic of traumatic fracture. The significantly reduced mechanical integrity in osteoporosis may originate from porosity and alterations to the intra/extrafibrillar structure, while the fibril deformation under treatment indicates improved nano-scale characteristics. In conclusion, losses in strength and fibril deformation at low strain rates correlate with the occurrence of fragility fractures in osteoporosis, while improvements in structural and mechanical properties following bisphosphonate treatment may foster resistance to fracture during physiological strain rates.